1974
DOI: 10.1007/bf00117024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instructional objectives on learning and retention

Abstract: A synthesis is presented of the various rationales which predict the facilitative influence of instructional objectives on learning and retention. Facets which are particularly relevant to the analysis of instructional objectives in learning situations include the dimensional character of attending behavior, the optimal degree of specificity to be incorporated in specifying instructional outcomes, effects of the placement or position of objectives during instruction, and a discussion of investigations concerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recent research (Lawson, 1974) has indicated that it is by no means clear why, and under what circumstances, a statement of specific and general objectives may exercise a powerful and positive effect on learning. Presently available evidence (Hastings, 1972; Varuganam, 1971) suggests that student knowledge of objectives enhances learning.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research (Lawson, 1974) has indicated that it is by no means clear why, and under what circumstances, a statement of specific and general objectives may exercise a powerful and positive effect on learning. Presently available evidence (Hastings, 1972; Varuganam, 1971) suggests that student knowledge of objectives enhances learning.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently subjects concentrate on important points without specifically being instructed to do so. Lawson (1974) suggested that there is good evidence that providing specific objectives facilitates intentional learning (learning of materials related to objectives) but that their effect on incidental learning (learning of materials irrelevant to the objectives) is less clear. In a study by Jenkins and Neisworth (1973), performance on test items was consistently superior when the corresponding objectives were provided than when these objectives were not present.…”
Section: Objectivesmentioning
confidence: 97%
“…However, as recent research has suggested (Lawson, 1974) it is by no means clear why, and under what circumstances, a statement of objectives exercises the powerful and positive effects on learning that have been indicated. Factors involved certainly include the degree of specificity of objectives (Rothkopf and Kaplan, 1972) and the issue of whether or not they are communicated to students (Varuganam, 1971).…”
Section: Discussionmentioning
confidence: 93%